Challenges of non‐commercial multicentre North‐South collaborative clinical trials. Issue 2 (10th December 2012) - Ravinetto, Raffaella M.; Talisuna, Ambrose; De, Maaike; van, Harry; Menten, Joris; Van, Chantal; Tinto, Halidou; Gonzalez, Raquel; Meremikwu, Martin; Nabasuma, Carolyn; Ngoma, Ghyslain M.; Karema, Corine; et al.
Abstract The last decade has witnessed a substantial increase of multi‐centre, public health‐oriented clinical trials in poor countries. However, non‐commercial research groups have less staff and financial resources than traditional commercial sponsors, so the trial teams have to be creative to comply with Good Clinical Practices (GCP) requirements. According to the recent experience of a large multicentre trial on antimalarials, major challenges result from the complexity of multiple ethical review, the costs of in‐depth monitoring at several sites, setting up an adequate Good Clinical Laboratory Practices (GCLP) framework, lack of insurers in host countries, and lack of adequate non‐commercial data management software. Public research funding agencies need to consider these challenges in their funding policies. They also could support common spaces where North‐South collaborative research groups may share critical information, such as on research insurance and open‐source, GCP‐compliant software. WHO should update its GCP guidelines, which date back to 1995, to incorporate the perspectives and needs of non‐commercial clinical research.